ADA APA DENGAN KINERJA DI BANK PANIN DUBAI SYARIAH? - Ayu Setiyaningsih; Ida Haryanti; Kharis Fadlullah Hana (BanKu: Jurnal Perbankan dan Keuangan, 2020)
ABSTRACTEvery banking institution always tries to improve its performance in order to achieve the expected goals. To achieve these objectives a sound or non-performing loan financing or not problematic, qualified and competent human resources, and an increase in the value of the preparation of financial report. In banking law in carrying out business activities, bank must be guided by the precautionary principle set forth in the Banking Act. This study aims to determine the performance conditions at Bank Panin Dubai Syariah due to a fictitious credit case that occured. The research method used is qualitative data analysis and normative juridical approach. The results of the research that can be stated based on the research conducted is that the performance at Bank Panin Dubai Syariah experienced instability both from employee development, labor recruitment, and financial reports due to the occurrence of fictitious credit cases conducted by the president director of PT. Bank Panin Dubai Syariah. Ass well as in terms of financing experience a standstill due to the ineffectiveness of the application of the precautionary principle at the Bank Panin Dubai Syariah.Keywords: performance; fictitious credit; human resources; financial reports. ABSTRAKSetiap institusi perbankan selalu berusaha untuk meningkatkan kinerjanya guna mencapai tujuan yang diharapkan. Untuk mencapai tujuan tersebut diperlukan adanya pembiayaan kredit yang sehat atau tidak bermasalah, sumber daya manusia  yang berkualitas serta mumpuni, dan mengalami peningkatan nilai penyusunan laporan keuangan. Dalam hukum perbankan dalam menjalankan kegiatan usaha bank harus berpedoman pada prinsip kehati-hatian yang dituangkan dalam Undang-Undang Perbankan. Penelitian ini bertujuan untuk mengetahui kondisi kinerja di Bank Panin Dubai Syariah akibat adanya kasus kredit fiktif yang terjadi. Metode penelitian yang digunakan adalah analisis data kualitatif  dan pendekatan yuridis normatif. Hasil penelitian yang dapat dikemukakan berdasarkan penelitian yang dilakukan adalah kinerja di Bank Panin Dubai Syariah mengalami ketidakstabilan baik dari pengembangan karyawan, perekrutan tenaga kerja, dan laporan keuangan akibat telah terjadinya kasus kredit fiktif yang dilakukan oleh direktur utama PT. Bank Panin Dubai Syariah. Serta dari sisi pembiayaan mengalami macet dikarenakan belum efektifnya penerapan prinsip kehati-hatian di Bank Panin Dubai.Kata Kunci: kinerja; kredit fiktif; sumber daya manusia; laporan keuangan.